PENGGUNAAN ALAT BUKTI INFORMASI ELEKTRONIK DALAM PEMBUKTIAN TINDAK PIDANA NARKOTIKA DI ACEH. - Daniel Saputra, Mohd. Din, Mahfud. (Jurnal Ilmu Hukum, 2015)
Abstract: Article 86 (2) of the Act Number 35, 2009 regarding Narcotic in conjunction to Article 5, of the Act Number 11, 2008 regarding Information and Electronic Transaction is regulating the usage of the electronic information especially narcotic crime. The causes of lacking usage of the electronic information by law enforcers in proving narcotic crimes in Aceh result from firstly internal obstacle comprising of lack of knowledge from law enforcers and moral factor of the law enforcers. Secondly, it is external obstacle consisting of legal substance, criminal justice evidence system existing in Indonesia and people participation. Lacking of electronic information as the evidence in probing narcotic crime in Aceh (narcotic case only) that the decision has closed to the principle of justice despite the fact that it lacks the evidence, however the more evidences obtained by the investigators the closer to the fair judges’ decision would be. It is recommended that the law enforcers especially the investigators in Aceh in dealing with the case of narcotics (evidence matter), must present the evidence beside other evidences ant it can only be achieved by the increase of their knowledge and skills deep investigation either personally or institutionally through technical training (formal or non-formal) relating to the electronic information usage as the evidence of narcotic case. Keywords: Proving, Evidence, Narcotic Crime. Abstrak: Pasal 86 ayat (2) UU Narkotika jo. Pasal 5 UU ITE, diatur tentang penggunaan alat bukti informasi elektronik dalam pembuktian, khususnya tindak pidana narkotika. Penyebab tidak digunakannya alat bukti informasi elektronik dalam pembuktian tindak pidana narkotika di Aceh dikarenakan, yaitu Pertama kendala internal yang meliputi faktor pengetahuan dari penegak hukum dan faktor moral dari penegak hukum. Kedua, kendala eksternal yang meliputi subtansi hukum (legal subtance), sistem pembuktian yang berlaku di Indonesia dan partisipasi masyarakat. Ketiadaan informasi elektroni sebagai alat bukti dalam pembuktian tindak pidana Narkotika di Aceh, ada kalanya putusan tersebut sudah mendekati rasa keadilan, namun semakin banyaknya alat bukti yang dimiliki dalam pembuktian akan sangat menentukan terbitnya suatu putusan yang berkeadilan. Disarankan kepada penegak hukum khususnya penyidik di Aceh dalam menangani kasus tindak pidana narkotika (terkait pembuktian) wajib mengusahakan untuk menghadirkan alat bukti informasi elektronik dalam pembuktian di samping alat bukti konvensional lainnya dan hal tersebut akan dapat tercapai dengan peningkatan pengetahuan, skill, dan pendalaman baik secara personal maupun kelembagaan melalui pelatihan-pelatihan teknis (formal maupun non formal) terkait penggunaan informasi elektronik sebagai alat bukti dalam pembuktian tindak pidana narkotika. Kata kunci : Pembuktian, alat bukti informasi elektronik.